2017
DOI: 10.1111/ejh.12908
|View full text |Cite
|
Sign up to set email alerts
|

Deregulated expression of long non‐coding RNA UCA1 in multiple myeloma

Abstract: Our study suggests a possible prognostic impact of UCA1 expression levels on MM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 48 publications
0
34
0
Order By: Relevance
“…14 NEAT1 acts as an oncogene in many types of cancers as in breast cancer, non-small-cell lung cancer (NSCLC), 15 that modulate cancer progression in renal cell carcinoma through epithelial mesenchymal transition (EMT) 16 and regulate miR-449b-5p/c-Met axis in glioma pathogenesis. 17 Meanwhile, NEAT1 is significantly downregulated in leukemia, multiple myeloma, [18][19][20] and acute promyelocytic leukemia. 18 The aim of the present study was to evaluate the relative expression level of serum NEAT and MiR-129-5p in HCC patients among Egyptian population and their relation with patient's clinical and biochemical investigations.…”
Section: Neat1mentioning
confidence: 99%
See 1 more Smart Citation
“…14 NEAT1 acts as an oncogene in many types of cancers as in breast cancer, non-small-cell lung cancer (NSCLC), 15 that modulate cancer progression in renal cell carcinoma through epithelial mesenchymal transition (EMT) 16 and regulate miR-449b-5p/c-Met axis in glioma pathogenesis. 17 Meanwhile, NEAT1 is significantly downregulated in leukemia, multiple myeloma, [18][19][20] and acute promyelocytic leukemia. 18 The aim of the present study was to evaluate the relative expression level of serum NEAT and MiR-129-5p in HCC patients among Egyptian population and their relation with patient's clinical and biochemical investigations.…”
Section: Neat1mentioning
confidence: 99%
“…NEAT1 acts as an oncogene in many types of cancers as in breast cancer, non‐small‐cell lung cancer ( NSCLC), that modulate cancer progression in renal cell carcinoma through epithelial mesenchymal transition (EMT) and regulate miR‐449b‐5p/c‐Met axis in glioma pathogenesis . Meanwhile, NEAT1 is significantly downregulated in leukemia, multiple myeloma, and acute promyelocytic leukemia …”
Section: Introductionmentioning
confidence: 99%
“…14 Sedlarikova et al found that UCA1 was downregulated in MM patients, when compared to healthy donors. 58 Their results also revealed that higher levels of UCA1 were correlated to advanced ISS stage and 1q21 gain. Due to the fact that IL-6 contains a site for CREB binding, which results in the suppression of IL-6 autocrine secretion, the investigators assumed that higher UCA1 levels induce CREB suppression, and consequently, higher IL-6 secretion, which leads to the survival of MM cells, bone resorption, and M-Ig secretion.…”
Section: Uca1mentioning
confidence: 94%
“…In acute myeloid leukemia (AML), UCA1 promotes the proliferation of malignant cells by suppressing p27 kip1 . Sedlarikova et al found that UCA1 was downregulated in MM patients, when compared to healthy donors . Their results also revealed that higher levels of UCA1 were correlated to advanced ISS stage and 1q21 gain.…”
Section: Mechanisms Of Lncrnas In MMmentioning
confidence: 99%
“…LncRNA H19 was also upregulated in MM patients and cell lines, and the expression level in serum could assist clinical staging, which could roughly determine the severity of disease (Pan et al, ). LncRNA UCA1 was able to discriminate newly diagnosed MM patients and healthy donors with high sensitivity and specificity and higher levels were significantly associated with worse OS of MM patients during the 1–4 years follow‐up period (Sedlarikova et al, ).…”
Section: Values Of Targeting Ncrnas In MMmentioning
confidence: 99%